Effect of Fibers Orientation on the Nonlinear Dynamic Performance of Laminated Composite Plate under Different Loading In-plane - Wisam Hamzah Mohammed; Svetlana Shambina; Haider Kadhim Ammash (Civil Engineering Journal, 2022)
Non-linear dynamic analysis of a cross-ply laminated composite with fibre spacing plates under in-plane loading was presented. The mathematical formulation is based on first-order shear deformation theory and von-Karman non-linearity. Eight-node isoperimetric quadrilateral elements with five degrees of freedom per node were used to maintain geometric nonlinearity. In this investigation, a variety of fiber spacings and fibre orientations were used for the purpose of studying the effect of improvements on the behaviour of samples with this type of load. The dynamic equilibrium equations were solved using the Newmark integration technique. The non-linear dynamic analysis addressed several functions of changing fibre spacing with various changes in volume percentage and diverse fibre orientations. Fibre orientation, volume fraction fluctuation, and fibre distribution significantly affected laminated composite plates' non-linear dynamic behaviour. This study showed that the combination of improvements does not give a clear vision of the ideal improvement, and the best case for fibre distribution and the best case for layer rotation and combination should be studied to know the effect of the ameliorations one on the other and distinguish the impact of the transverse loading pattern in one direction on rotating the sample layers with axial load in one direction, so that changing the fibre distribution is more effective in the behaviour and stability of the plate by taking advantage of the orientation change, as demonstrated in this paper. Doi: 10.28991/CEJ-2022-08-12-03 Full Text: PDF